A contribution to full-scale high fidelity aircraft progressive dynamic damage modelling for certification by analysis. Issue 3 (4th May 2019) - Song, Yangkun; Horton, Brandon; Perino, Scott; Thurber, Andrew; Bayandor, Javid
ABSTRACT: The era of powered flight began with the introduction of the first flying machine in 1903. Sadly, less than two years later, the first fatal accident in a powered aircraft occurred. Motivated in part by this early tragedy, engineers have raised aerospace standards so that air travel is now the safest means of mass transit in the world. However, unplanned landings on unanticipated surfaces continues to pose an ever-present risk of casualty, due in-part to a lack of understanding about such interactions. The experimental characterisation of full-scale airframe crashworthiness has traditionally been cost-prohibitive and therefore rare. In an effort to complement current airframe certification requirements and contribute towards certification-assisted analysis, this paper presents a partially validated comprehensive numerical methodology. This methodology is applied to assess the progressive structural damage resulting from a full-scale aircraft model impacting soft and hard surfaces with comparison to a real-life commercial aircraft crash landing test.